PENGGUNAAN FITUR SHOPEE PAYLATER BAGI MAHASISWA FISIP UNRI - Artiga "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Globalization has in fact become one of the major components as a driver of the world to be more advanced, especially in the field of technology. In the current era technology has developed very rapidly as evidenced by the birth of Financial Technology (fintech), one of which is a Paylater that relies on the label of an application called Shopee Paylater. Life Style from a shopping style is a proof of self-image for the surrounding environment. This study was conducted to find out more about online shopping behavior using the Shopee Paylater feature in adolescents, especially students of the Faculty of Social and Political Sciences, Riau University. This study uses a qualitative descriptive research method using a phenomenological approach. The results of the study wereobtained from interviews with resource persons and also using comparisons from studies that have been studied previously. The influence of lifestyle and social in fact really greatly affects the use of Shopee Paylater and also affects the behavior or shopping behavior patterns of students of the Faculty of Social and Political Sciences, University of Riau. Paylater itself is centered or intended to focus more on students with all the worries that often occur at the end of the month. Students who tend to like shopping with Shopee Paylater make their lifestyle more consumptive, and the use of Shopee Paylater occurs because of social influences todevelop self-image, friends or close relatives, as well as the advantages offered from the Shopee application. Keywords: Life Style, Shopee Paylater, Students